Burnout Syndrome, anxiety, academic performance and self-declared characteristics of business students - Lima, Gabrieli Alves de (2022)
The student's academic experience may be harmed when the individual's physical and mental capacity is affected. In this context, we try to analyze the difference between Burnout Syndrome and anxiety based on the self-declared characteristics of buseness students and their academic performance, as well as to identify the relationship between Burnout syndrome and anxiety. The study aims to provide evidence to educational institutions about academic performance, Burnout syndrome and anxiety, in order to support actions to promote a more harmonious teaching-learning process. A survey was applied using the State-Trait Anxiety Inventory, the Copenhagen Burnout Inventory – Student Version, and the Academic Income Coefficient (CRA), with 126 students from a Public University. Data were treated using Mann-Whitney, Kruskal-Wallis and Linear Regression tests. The findings illustrate that (i) there is a significant difference between the levels of Burnout and the course, gender, period, and marital status of the respondent; (ii) anxiety levels show differences when compared between course and sex; and (iii) anxiety can explain the levels of Burnout Syndrome. These results can be used to guide relationships in the socio-academic environment and in the development of wellness policies.